Soil Remediation by Nanotechnology: Valuating Materials, Mechanisms, and Environmental Impacts - Hoareau, Carol Emilly; Kabeya, Clementine (Industrial and Domestic Waste Management, 2024)
The rapid growth of the human population and industrial activities has resulted in considerable environmental degradation. Processes such as industrialization, mining, agriculture, and waste disposal introduce harmful chemicals that contaminate soil, groundwater, and surface waters. Consequently, soil remediation has become a critical priority for many nations, given that soil quality directly affects agriculture and public health. Nanotechnology presents promising solutions to the shortcomings of traditional soil remediation methods by offering innovative materials and mechanisms for the removal or neutralization of contaminants. This review intends to evaluate the use of nanotechnology in soil remediation, emphasizing the nanomaterials employed, their reaction mechanisms, and potential environmental effects. Nanomaterials like nano zero-valent iron, metal oxides, and carbon-based materials have shown effectiveness in immobilizing, degrading, or extracting pollutants from soil and water through processes such as adsorption, photocatalysis, and filtration. However, certain nanomaterials raise concerns about toxicity and bioaccumulation, which may negatively affect ecosystems and human health. Therefore, additional research is needed to confirm the safety, compatibility, and sustainability of these technologies. This review also identifies significant challenges in the implementation of nanotechnologies for soil remediation and examines future directions and recommendations for addressing these challenges.